2020
DOI: 10.1007/s10640-020-00455-8
|View full text |Cite
|
Sign up to set email alerts
|

Buy Coal or Kick-Start Green Innovation? Energy Policies in an Open Economy

Abstract: This paper analyses two unilateral policies available to countries that want to rapidly curb carbon emissions in the global economy, but do not own any fossil fuel resources. If fossil fuel owners do not cooperate in CO 2 emission reduction efforts, the only strategy to reduce their fossil fuels' use is to exploit the interconnectedness of production given by international trade. We compare a Pigouvian approach, namely a subsidy for renewable energy prices, and a Coasian supply-side strategy, buying extractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…It can be concluded that in companies intending to develop eco‐friendly supply chain management, ‘innovation’ plays an important role; hence, more investment in this area is required. The findings of Ravetti et al (2020) also acknowledged that ‘innovation’ has a positive and direct impact on the company's environmental performance. As such, companies in polluting industries need innovation to stay active in a competitive market (Ravetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that in companies intending to develop eco‐friendly supply chain management, ‘innovation’ plays an important role; hence, more investment in this area is required. The findings of Ravetti et al (2020) also acknowledged that ‘innovation’ has a positive and direct impact on the company's environmental performance. As such, companies in polluting industries need innovation to stay active in a competitive market (Ravetti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Ravetti et al (2020) also acknowledged that ‘innovation’ has a positive and direct impact on the company's environmental performance. As such, companies in polluting industries need innovation to stay active in a competitive market (Ravetti et al, 2020). On the other hand, the results imply that in companies that aim to mitigate the negative effects of their products on the environment, ‘technologies for cleaner production’ has a significant influence that assists their supply chain in becoming environmentally sustainable; therefore, investments in technologies are essential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to reduce the effects of climate change and increase the decarbonization of the world's economies by reducing air emissions, greening production, and expanding the use of alternative energy sources is taken into account by most countries. The transformation of the global energy sector plays a special role in achieving these goals (Xie et al, 2020;Lorente et al, 2020;Ravetti et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, Odam and de Vries (2020) suggest that governments should carefully implement RERs policies guided by learning curve estimation. The more common RERs policies include low-carbon policies (Wendling et al, 2020), RERs production subsidies (Ravetti et al, 2020), RERs portfolio standards (Wendling et al, 2020), clean energy-related economic policies (Chen and Kim, 2020), and so on. At present, the application of RERs is recognized by the vast majority of residents in most of developing countries, and they have a willingness to consume RERs.…”
Section: Introductionmentioning
confidence: 99%